ANALISIS PERAN PEMIMPIN DALAM MEMOTIVASI DAN MENGAWASI KARYAWAN (PT SURINDO TEGUH GEMILANG) - Mohamad Ferdiansyah; Sri Lestari (PUTRA JAWA PUBLISHER, 2023)
This research was conducted to determine the role of a leader within a company, which includes providing motivation and supervision to employees. Supervision is highly important for leaders to help employees anticipate irregularities, ensuring that the company follows its plans and achieves the goals set by PT Surindo Teguh Gemilang. This study employs a qualitative method using a descriptive approach. The author analyzes the role of leaders in motivating and supervising employees at PT Surindo Teguh Gemilang. The research was conducted on-site to directly examine the actual situation, ensuring the collection of accurate data. Data collection involved the use of interview methods to gather information about the significant impact of leaders' roles within the company. The study also involved an in-person observation of the company's premises at PT Surindo Teguh Gemilang. The results of the research conducted at PT Surindo Teguh Gemilang underscore the critical importance of leaders' roles in motivating and supervising employees. These roles significantly influence employee performance, leading to either improvement or deterioration. Effective supervision also holds great importance for PT Surindo Teguh Gemilang as it directly affects employee performance. Adequate supervision encourages employees to be more diligent and disciplined in their work.